KUALITAS IBADAH DAN INTENSITAS AMAR MA’RUF NAHI MUNKAR DALAM SPEKTRUM RELIGIUSITAS PRIBADI MUSLIM - Muhammad Fatchurrohman (MAMBA'UL 'ULUM, 2018)
Quality of Worship and Intensity of Amar Ma’ruf Nahi Munkar in Muslim Personal Religiousity Spectrum. Islam as dienullah is the most perfect religion. Islam has the practice of completely surrendering to Allah, it is the core attitude of Muslim personal riligiusitas and the realization of noble morality (mahmudah). Understanding and reintroducing Islamic teachings is one of the aspects that must be considered is the quality of worship and the importance of being in the way of marriage. This has actually been widely known by Muslims, so what is needed is how to implement and sharpen the sense of religion towards self and others so that it becomes a driver and encouragement in preaching. Da’wah can be interpreted as the process of delivering Islamic religion to mankind. In a process of da’wah it is not only a conveying endeavor, but an attempt to change the way of thinking, the way of feeling, the way of life, the human being is the target of the mission towards the better. The quality of worship and success in preaching are finally seen when behavior is a reflection of faith. So sincerity in devotion to God will be biased to the spirit of work ethic both in the realm of human relations with God and the relationship between humans and humans (hablun minallah wa hablun minannas). This is where the meeting point between the quality of worship and the spirit of preaching in the spectrum of one’s religious reality.